Measurement of Successful Leadership via a Nine Factor Model on Bank Profit – A Case of Vingroup in Real Estate Industry in Vietnam - Tran Ngoc Huy, Dinh; Dac Anh Chuong, Nguyen (International Journal of Psychosocial Rehabilitation, 2020)
Vingroup (VIC) has been gaining achievements with VinFast (cars), VinSmart, and Vinpearl, and Vinhomes has made very positive contributions to the overall achievements of the real estate sector and industries, deserving of its position as one of the leading groups contributing to the economy. Movement of net profit under the impacts of cost, stock price, and many other factors will reflect the business health of Vingroup and the real estate industry. Good business management requires us to consider the impacts of multiple macro and micro factors on VIC net profit, and it contributes to promoting business plans and economic policies for economic growth and stabilizing macroeconomic factors. By data collection method through statistics, analysis, synthesis, comparison, and quantitative analysis to generate qualitative comments and discussion, using econometric methods to perform regression equations and evaluate quantitative results, the article analyzed and evaluated the impacts of NINE (9) macroeconomic factors such as stock price, VNIndex, risk-free rate, lending rate, inflation, GDP growth, S&P500, exchange rate, etc. on the net profit of a leading real estate firm, Vingroup (VIC), in Vietnam in the period of 2010-2019, both positive and negative sides. The results of quantitative research, in an eight-factor model, show that the increase in inflation and lending rate and the reduction in risk-free rate have a significant effect on reducing VIC net profit with the highest impact coefficient; the second is decreasing cost. Last but not least, we recognize that VIC net profit responds much more to the yield of government bonds compared to Vinamilk (a leading firm in the F&B industry). This research finding and recommended policy also can be used as a reference in policy for real estate systems in many developing countries.